2015
DOI: 10.1007/s11548-015-1264-4
|View full text |Cite
|
Sign up to set email alerts
|

An endoscopic structured light system using multispectral detection

Abstract: Purpose In clinical examinations, the tissue surface topology is an important feature for detecting the tissue pathology and implementing augmented reality. We have previously presented a miniaturised structured light (SL) system for recovery of tissue surface shape in minimally invasive surgery (MIS), based on a flexible multispectral structured illumination probe (1.9 mm diameter) [1]. This paper reports further hardware and analytical developments to improve the light pattern decoding result and increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Previously, a SL-enabled 3D tissue surface shape and hyperspectral imaging system was presented [4,5]. This used an optical fiber bundle with the fibers arranged in linear and circular arrays, respectively, at either end ( Fig.…”
Section: Arxiv:170606081v2 [Cscv] 21 Jun 2017mentioning
confidence: 99%
“…Previously, a SL-enabled 3D tissue surface shape and hyperspectral imaging system was presented [4,5]. This used an optical fiber bundle with the fibers arranged in linear and circular arrays, respectively, at either end ( Fig.…”
Section: Arxiv:170606081v2 [Cscv] 21 Jun 2017mentioning
confidence: 99%
“…Table 1 shows that the pattern decoding algorithm functions robustly with both the phantom and even some challenging ex vivo data, with feature matching sensitivity higher than 0.8, and precision 0.99. Compared with previous work [13], this shows a much higher sensitivity for feature matching due to the high spot detection accuracy achievable with FCN. Meanwhile, the near real-time performance of FCN guarantees its real-world practicality.…”
Section: Experiments and Resultsmentioning
confidence: 77%
“…Previous work has shown that the projected spot patterns are robust to changes in background albedo, due to their narrow bandwidth [11]. It was also found that, given an accurate calibration and perfect feature matching, reconstruction error can reach 0.7 mm at a working distance of ~10 cm [13]. Thus, the reconstruction accuracy mainly depends on the pattern decoding results.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Image size, contrast and color balance adjustment have been available [5]. Additional computer techniques for real-time enhancement of surgical images include spatial frequency modulation (filtering) [72, 73], tissue topology and texture recognition [74], adaptive illumination adjustment [75] and image stabilization [76].…”
Section: Emerging Technologymentioning
confidence: 99%